REVITALISASI PERMUKIMAN KUMUH KAMPUNG PULO, KECAMATAN KAMPUNG MELAYU, JAKARTA TIMUR - Ziyad Fauzi Na'im; Budi A. Sukada (Jurusan Arsitektur dan Perencanaan, 2022)
Slums are synonymous with advanced cities, especially the city of Jakarta, from the many beauty and progress that exist, it has many problems, one of which is the arrangement of slum settlements which are still widely spread in important areas such as the economic center, one of which is Kampung Pulo which is in the economic center of East Jakarta and also has a special plan to be developed, while previously in 2015 there were clashes due to the plan for relocation of settlements on the banks of the Ciliwung river besides that many of those who had been relocated did not feel better with their lives even though they lived in new, better buildings and cleaner. The problem is the location of their settlement which is on the banks of the Ciliwung river so that it does not have an infiltration area in the Kampung Pulo settlement. To solve this problem, the government has prepared land for the new Kampung Pulo settlement so that the existing problems in this area can be reduced or eliminated, one of which is flooding in the Kampung Pulo settlement. they are alive and do not have a negative impact on the environment and the Ciliwung river. There has been a lot of research approach data about Kampung Pulo regarding their way of life on the Ciliwung river so that it can be applied to the completion of the revitalization of the new Kampung Pulo settlement in an area that has been planned by the government by using a typology analysis of settlement architecture so that it can be a solution for designing the revitalization of Kampung Pulo. Keywords: Revitalitation ; Slum Houses; Typology Abstrak Permukiman kumuh identik dengan perkotaan yang maju terutama kota Jakarta dari sekian banyak keindahan dan kemajuan yang ada memiliki banyak permasalahan di dalamnya salah satunya penataan permukiman kumuh yang masih banyak tersebar di area penting seperti pusat perekonomian salah satunya Kampung Pulo yang berada di pusat perekonomian Jakarta Timur dan juga memiliki perencanaan khusus untuk di kembangkan, sementara sebelumnya pada tahun 2015 sempat terjadi bentrok akibat rencana relokasi permukiman di bantaran kali Ciliwung ini selain itu banyak dari mereka yang telah terelokasi tidak merasa lebih baik dengan kehidupan mereka walaupun mereka tinggal di bangunan baru yang lebih baik dan lebih bersih. Permasalahan pada lokasi permukiman meraka yang berada di bantaran sungai Ciliwung sehingga tidak memiliki area resapan pada permukiman Kampung Pulo. Untuk menyelesaikan permasalahan ini pemerintah telah mempersiapkan lahan untuk pemrukiman Kampung Pulo yang baru sehingga permasalahan yang ada pada area ini bisa dikurangi ataupun dihiklangkan salah satunya banjir langanan pada permukiman Kampung Pulo.Pendekatan kebiasaan hidup mereka perlu diperhatikan untuk bisa membentuk ruang kampung yang baru sehingga mendukung cara mereka hidup dan tidak memberikan dapak negatif pada lingkungan dan sungai Ciliwung. Sudah banyak data pendekatan penelitian tentang kampung Pulo ini mengenai cara hidup mereka di batarana sungai Ciliwung sehingga bisa terapkan pada penyelesaian revitalisasi permukiman Kampung Pulo yang baru di area yang sudah direncanakan oleh pemerintah dengan penggunaan analisa tipologi arsitektur permukiman sehingga bisa menjadi solusi untuk perancangan revitalisasi Kampung Pulo.